Triggering receptor expressed on myeloid cells-2 expression in the brain is required for maximal phagocytic activity and improved neurological outcomes following experimental stroke - Kurisu, Kota (J Cereb Blood Flow Metab, 2018)
Triggering receptor expressed on myeloid cells-2 (TREM2) is an innate immune receptor that promotes phagocytosis by myeloid cells such as microglia and macrophages. We previously showed that TREM2 deficiency worsened outcomes from experimental stroke and impeded phagocytosis. However, myeloid cells participating in stroke pathology include both brain resident microglia and circulating macrophages. We now clarify whether TREM2 on brain microglia or circulating macrophages contribute to its beneficial role in ischemic stroke by generating bone marrow (BM) chimeric mice. BM chimera mice from TREM2 knockout (KO) or wild type (Wt) mice were used as donor and recipient mice. Mice were subjected to experimental stroke, and neurological function and infarct volume were assessed. Mice with intact TREM2 in brain microglia showed better neurological recovery and reduced infarct volumes, compared with mice lacking microglial TREM2. Myeloid cell activation and numbers of phagocytes were decreased in mice lacking brain TREM2, compared with mice with intact brain TREM2. These results suggest that TREM2 expression is important for post-stroke recovery, and that TREM2 expression on brain resident microglia is more essential to this recovery, than that of circulating macrophages. These findings might suggest a new therapeutic target for cerebrovascular diseases.